HMGB1 is a mediator of cuproptosis-related sterile inflammation - Liu, Jiao; Liu, Yang; Wang, Yuan; Kang, Rui; Tang, Daolin (Frontiers in Cell and Developmental Biology, 2022)
Cuproptosis is a recently recognized modality of cell death driven by intracellular copper-dependent mitochondrial stress. However, the mediators of the sterile inflammatory response to cuproptotic death are undetermined. Here, we report that high-mobility group box 1 (HMGB1), a damage-associated molecular pattern, is released by cuproptotic cells to initiate inflammation. Mechanically, copper accumulation-induced adenosine triphosphate (ATP) depletion activates AMP-activated protein kinase (AMPK) to promote HMGB1 phosphorylation, resulting in increased extracellular release. In contrast, genetic (using RNAi) or pharmacologic (using dorsomorphin) inhibition of AMPK activation limits cuproptosis and HMGB1 release. Functionally, the ability of HMGB1-deficient cuproptotic cells to promote advanced glycosylation end product-specific receptor (AGER, also known as RAGE)-dependent inflammatory cytokine production is greatly reduced. Thus, HMGB1 is a key immune mediator of cuproptosis-initiated sterile inflammation.